2021
DOI: 10.1089/acm.2020.0298
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Rater Reliability of Kampo Diagnosis for Chronic Diseases

Abstract: This single-center observational study aimed to assess the inter-rater reliability (IRR) of Kampo medicine pattern diagnosis, which is modularized into three modules for chronic diseases, using 64 participants' information documents. The linearly weighted percentage of agreement and Gwet's agreement coefficient (AC) 2 for the deficiency-excess module, among three specialists, were 85.9% and 0.708, respectively. The unweighted percentage of agreement and Gwet's AC1 were 64.6% and 0.542 for the cold-heat, and 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…All the participating physicians are board-certified specialists in Kampo medicine who also have active conventional medicine licenses. Inter-rater reliability of some of these physicians has been shown previously (Maeda-Minami et al, 2021).…”
Section: Participantsmentioning
confidence: 83%
See 1 more Smart Citation
“…All the participating physicians are board-certified specialists in Kampo medicine who also have active conventional medicine licenses. Inter-rater reliability of some of these physicians has been shown previously (Maeda-Minami et al, 2021).…”
Section: Participantsmentioning
confidence: 83%
“…This pattern diagnosis was given without regard to the CM diagnosis and was made independently using the TM evaluation. We did consider pattern diagnosis interrater reliability when considering our study's wider internal validity, however a study done previously by our group indicated this was not a major concern (Maeda-Minami et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This term originated from the ancient Chinese medical textbook "Huangdi Neijing" about 2000 years ago. The continuous implementation of ME-BYO measurement from a young age makes it possible to extend the healthier life expectancy and reduce medical expenses [149][150][151]. To avoid being ME-BYO, sleeping well, performing moderate exercise, and eating a healthy diet are important.…”
Section: Foods With Anti-ageing Effectsmentioning
confidence: 99%
“…In addition, patients with two or more risk factors of metabolic syndrome, including visceral fat obesity, diabetes, hypertension, and dyslipidaemia, tend to experience the onset of deadly heart and cerebrovascular diseases. Therefore, these high-mortality diseases can be prevented by removing these risk factors [91][92][93].…”
Section: The Idea Of Me-byo (Mibyou)mentioning
confidence: 99%